Rhoda: 'Comrade Kadalie, You Are Out of Order! A Biography - Pollak, Joel B. (UJ Press, 2023)
This authorized biography was made possible through the gracious help of my mother-in-law, Rhoda Kadalie, who provided generous access to her files, letters, photographs, and extensive library of documents. She made time to sit with me for several hours of interviews from September through October 2021, to answer questions as they arose, and to offer innumerable clarifications. Rhoda also reviewed the first draft of the biography in December 2021, making corrections and additions, and contributing some of her own original vignettes, never before published.